A tribute to a lady of excellence - Wee, Cindy (UiTM Sarawak, 2004)
Prof. Dr. Azni's passion in research started after she completed her masters in solar energy in 1989. It was a turning point in her career as she began her journey of research. She did further research ( for a PhD ) on solar energy, a very much male dominated field. After many years of hard work and presentations in many international conferences, she managed to establish a wide network in the area of her interest. She explains "all these roll on and keep the momentum going". Research has become part of her and she enjoys it thoroughly.